Comparison of hydrability, antioxidants, microstructure, and sensory quality of barley grass powder using ultra‐micro‐crushing combined with hot air and freeze drying. Issue 4 (5th February 2021) - Zhou, Wei; Cao, Xiaohuang; Islam, Md. Nahidul; Zheng, Huiting; Li, Jihua; Liu, Fei; Cao, Yupo; Dai, Yaping
Abstract: To explore the physicochemical characters of barley grass, ultra‐micro‐crushing (UMC) technology combined with air drying or freeze drying was carried out. After barley grass was air‐dried at 70°C or freeze‐dried at 15°C, it was grinded for 30, 60, 90, and 120 min using UMC, respectively. After combined processing, moisture content, particle size, odor, color, microstructure, water and oil‐holding capacity, the content of flavonoid and chlorophyll, water activity, and sensory qualities were determined. The particle size of barley grass powder decreased, and lightness value was increased; water and oil‐holding capacity decreased significantly ( p ≤  .05), whereas swelling and dissolving capacity increased in the processed grass powder. On the other hand, the total flavonoid content increased significantly ( p  ≤ .05). Barley grass odor features sulfide aroma, and its microstructure demonstrates lamellar morphology with some fewer fragmented pieces. The results suggested combined UMC at 90–120 min will be suitable for processing barley grass powder. Abstract : UMC technology combined with different drying methods has a great progress in the future processing of barley grass powder.